(untitled) (Architecture Image Studies, 2025)
This study analyzes the impact of integrating gamification and Universal Design for Learning (UDL) as inclusive strategies to enhance motivation and academic performance in diverse educational settings. The research followed a mixed-methods approach, combining a non-experimental quantitative correlational design with a qualitative descriptive-interpretative component. The sample consisted of 120 upper basic and high school students from urban institutions in Ecuador, who participated in an eight-week pedagogical intervention based on gamified activities structured under UDL principles. Data collection involved Likert-scale questionnaires, academic records, semi-structured interviews, and non-participant classroom observation. Results showed a significant increase in students’ motivation levels, with improvements across cognitive, affective, and behavioral dimensions. Additionally, the average grades rose by 14%, and a positive and significant correlation was found between motivation and academic performance (r = 0.72, p < 0.01). Qualitative findings complemented these outcomes, highlighting students’ perceptions of inclusion, enthusiasm, and active participation. In conclusion, the convergence of gamification and UDL emerges as an effective pedagogical strategy to promote inclusive education by fostering student engagement, diversifying learning experiences, and supporting academic success in heterogeneous contexts.